L'architecture de la Gaule romaine - Les fortifications militaires - Reddé, Michel; Brulet, Raymond; Fellmann, Rudolf; Haalebos †, Jan-Kees; Von Schnurbein, Siegmar; Aupert, Pierre (Documents d'archéologie française, 2006)
Seventy years after the publication of Volume 1 of Albert Grenier's Manuel d'archéologie gallo-romaine, Michel Reddc, Raymond Brulet, Rudolf Fellmann, Jan Kces Haalebos and 5iegmar von Schnurbein have prepared a new overview of Roman military architecture in the provinces of Gaul and Germania. The first part analyzes the different types of construction techniques observed in military camps, placing the development of this architecture within its historical context, from the conquest of Gaul to the middle of the fifth century AD. The second part is a catalogue which, while making no claim to be exhaustive, presents all the key sites alongside other lesser-known ones, especially in France. Each well- documented and systematically well-illustrated notice is augmented by a bibliography.